2005
DOI: 10.1051/forest:2005060
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration of a declining Quercus robur (L.) stand from 1999 to 2001. II. Daily actual evapotranspiration and soil water reserve

Abstract: -The components of actual evapotranspiration (ET) -interception (In%), tree transpiration (T) and forest floor ET -were measured from 1999 to 2001 in a mixed stand dominated by declining pedunculate oaks. Sap flux density measurements (oaks and maple) and forest floor ET [38] were extrapolated to season and stand scales by regressions with potential evapotranspiration (PET) and leaf area index (LAI). Stand ET varies between 383 and 594 mm (ET/PET: 0.75-1.23). Oak transpiration (21-38% of stand transpiration) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In that sense, forest ET can be considered to be a conservative process with a shifting role of the overstorey versus understorey contribution. The thinned versus control stands of Vincke et al (2005) indeed show a similar total ET, but a variable contribution of the understorey (Table S4). Black and Kelliher (1989) and Wilson et al (2000) provide insightful reviews on the factors controlling understorey ET.…”
Section: Overview Of Values Published In the Literaturementioning
confidence: 78%
See 1 more Smart Citation
“…In that sense, forest ET can be considered to be a conservative process with a shifting role of the overstorey versus understorey contribution. The thinned versus control stands of Vincke et al (2005) indeed show a similar total ET, but a variable contribution of the understorey (Table S4). Black and Kelliher (1989) and Wilson et al (2000) provide insightful reviews on the factors controlling understorey ET.…”
Section: Overview Of Values Published In the Literaturementioning
confidence: 78%
“…Although our data do not allow testing directions of effects, we assume that the negative correlations between overstorey and understorey functioning, as revealed by several of the reviewed studies (e.g. Jarosz et al, 2008;Vincke et al, 2005), are mainly a result of the mechanisms visualized in Figures 2 and 3 and not attributable to a feedback effect. However, our data do suggest that the effect of the understorey on tree regeneration cannot be neglected (Section 3.4), but whether these effects will alter overstorey functioning in the long term remains understudied (but see Thrippleton, Bugmann, & Snell, 2017).…”
Section: Re S P On S E To G Lobal Chang Ementioning
confidence: 87%
“…Previous studies reported similar LAI values for Belgium. Maximum LAI reached 2.5 m 2 m -2 in a 70 year old pedunculate oak stand (Gond et al 1999), 1.9-2.8 m 2 m -2 in a (declining) oak forest (Vincke et al 2005), 4-5.5 m 2 m -2 in a 90 year old beech stand (Aubinet et al 2002) and 3.5 m 2 m -2 in a mature mixed oak-beech stand (Mussche et al 2001). …”
Section: Overall Lai Dynamicsmentioning
confidence: 98%
“…Thinning usually implies a higher water availability for remnant trees because a lower water interception and transpiration, resulting in a diminution of length and intensity of water stress [46]. This is especially relevant in dehesas, where the survival of trees facing severe drought conditions is only possible if the tree root system extends beyond the influence of the tree canopy [20].…”
Section: Lateral Water Uptake By Treesmentioning
confidence: 99%